(untitled) (World Economics and Finance Bulletin, 2023)
The main development trends in the vegetable market of the world countries are studied in the article. In Uzbekistan, it has been determined that the population should increase their consumption of vegetables. Trend models were obtained based on the SPSS Statistical software package on changes in the consumption of vegetables by the Uzbekistan population. Based on the obtained trend models, the population consumption of vegetables until 2026 is forecasted.